2004
DOI: 10.1074/jbc.m312219200
|View full text |Cite
|
Sign up to set email alerts
|

Interferon α-induced Apoptosis in Tumor Cells Is Mediated through the Phosphoinositide 3-Kinase/Mammalian Target of Rapamycin Signaling Pathway

Abstract: Interferon (IFN) ␣ induces a caspase-dependent apoptosis that is associated with activation of the proapoptotic Bak and Bax, loss of mitochondrial membrane potential, and release of cytochrome c. In addition to the onset of the classical Jak-STAT pathway, IFN␣ also induced phosphoinositide 3-kinase (PI3K) activity. Pharmacological inhibition of PI3K activity by Ly294002 disrupted IFN-induced apoptosis upstream of mitochondria. Inhibition of mTOR by rapamycin or by overexpression of a kinase dead mutant of mTOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
103
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 40 publications
2
103
1
Order By: Relevance
“…Work from others has also implicated mTOR in the regulation of IFN-induced apoptosis (10), while in recent studies using cells with targeted deletion of both the Akt1 and Akt2 genes, we established Akt as a critical element of the IFN-signaling pathway required for engagement of mTOR and for mRNA translation of IFN-regulated genes (12,25). Together, the emerging evidence points toward an essential role for mTOR and its effectors in the generation of the biological effects of IFNs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Work from others has also implicated mTOR in the regulation of IFN-induced apoptosis (10), while in recent studies using cells with targeted deletion of both the Akt1 and Akt2 genes, we established Akt as a critical element of the IFN-signaling pathway required for engagement of mTOR and for mRNA translation of IFN-regulated genes (12,25). Together, the emerging evidence points toward an essential role for mTOR and its effectors in the generation of the biological effects of IFNs.…”
Section: Discussionmentioning
confidence: 91%
“…However, beyond the classic Jak-Stat pathways, there is evidence that IFNs activate several other signaling cascades, including the mTOR-regulated (8)(9)(10)(11)(12) and mitogen-activated protein kinase (MAPK) signaling cascades (13)(14)(15). Such non-Stat pathways play important roles in the induction of IFN-responses, via their ability to promote optimal IFN-dependent gene transcription (13) or mRNA translation of ISGs (12).…”
mentioning
confidence: 99%
“…On one hand, rapamycin is proved to be proapoptotic, especially in cancers, resulting in apoptotic death of the cancer cells 29. On the other hand, some evidence has demonstrated that rapamycin can be antiapoptotic 30, 31. For example, rapamycin inhibits death of syncytia via inhibition of proapoptotic Bax and inhibition of the mitochondrial cell death pathway 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have suggested a potential mechanism by which IFNs regulate translational control of IFN-specific genes, but the precise functional relevance of mTOR and downstream pathways in IFN signaling had not been defined. A recent study has suggested that mTOR signals may play positive roles in the generation of IFN biological responses, as evidenced by the inhibition of IFN␣-induced apoptosis in cells in which a kinase-deficient mTOR mutant was expressed or by treatment of cells with the mTOR inhibitor rapamycin (49). However, the functional relevance of specific effectors downstream of mTOR that may be involved in the generation of IFN responses has remained unknown to date.…”
Section: Discussionmentioning
confidence: 99%